Pricing of Outer Performance Option under a Two-Factor Stochastic Volatility Jump-Diffusion Model - Li, Wenmei (Journal of Global Economy, Business and Finance, 2025)
This study addresses the pricing of outer performance option within the framework of a two-factor stochastic volatility jump-diffusion model. By integrating martingale theory, partial differential equation (PDE) techniques, the Feynman-Kac theorem, and the Fourier inversion transform, we derive a semi-closed-form pricing formula for outer performance option. The methodology rigorously accounts for both stochastic volatility components and jump risk, thus providing a comprehensive solution to the complex valuation problem.